TAKDIR DAN KEBEBASAN MENURUT FETHULLAH GÃLEN - Haderi, Anang (TEOLOGIA, 2014)
Abstract:Destiny and free will is one of issues in Islamic theology which is still discussed by Moslem theologian up to now. This discussion has yielded some streams with its argumentation respectively. Included who intense to discuss this issue is muá¸¥ammad Fethullah GÃ¼len. At a glance, he offers to explain the issue in his own way without following one of the streams. He introduces some key terms, like ImÄm MubÄ«n, KitÄb MubÄ«n, Lauá¸¥ Maá¸¥fÅ«áº, Formal or Theoretical Destiny, actual destiny. Terms are GÃ¼lenâs exclusive. The article will elaborate the explaination of GÃ¼len relating to the destiny and free will. The purpose is to map what is he follows the streams or he has interpretation in himself. For this reason, I will spread out briefly views of theologian before, i.e. these streams of Muâtazili, al-Asyâarite, MatÅ«ridite Samarkand dan MatÅ«ridite BukhÄrÄ. By this way it will be seen clearly where is the position of GÃ¼len and what is contribution of his thinking.Abstrak: takdir dan kebebasan adalah isu teologi Islam yang masih diperbincangkan oleh para teolog hingga sekarang. Perdebatan ini telah melahirkan berbagai aliran dengan pen-dapatnya masing-masing.Termasuk yang juga intens mem-bahas isu ini adalah Muá¸¥ammad Fethullah GÃ¼len. Sekilas, ia berusaha menjelaskan isu ini dengan caranya sendiri tanpa mengikuti salah satu aliran tersebut. Ia mengenalkan beberapa istilah kunci, seperti ImÄm MubÄ«n,KitÄb MubÄ«n, Lauá¸¥ Maá¸¥fÅ«áº, takdir formal, takdir teoritis, dan takdir aktual. Istilah-istilah ini merupakan khas GÃ¼len. Tulisan ini akan mengelaborasi penjelasan GÃ¼len mengenai takdir dan kebebasan tersebut. Tujuannya adalah memetakan apakah ia mengikuti aliran-aliran teologi yang sudah ada ataukah ia penulis akan memaparkan secara singkat pendapat para teolog sebelumnya, yakni aliran-aliran Muâtazilah, al-Asyâariyah, MÄtÅ«ridiyah Samarkand dan MÄtÅ«ridiyah BukhÄrÄ. Dengan cara ini akan terlihat dengan jelas di manakah posisi GÃ¼len dan apa kontribusi dari pemikirannya itu.Keywords:ImÄm MubÄ«n,KitÄb MubÄ«n, Lauá¸¥ Maá¸¥fÅ«áº, takdir formal, takdir aktual.mempunyai pemaknaan sendiri terhadap persoalan ini. Untuk alasan ini,